The Determinants of User's Information Technology Acceptance: An Empirical Study on Higher Education - Darsono, Licen Indahwati (Kajian Manajemen dan Bisnis, 2009)
The fast growing acquisition and implementation of innovative IT applications are proliferated in business and non-business organizations. The mixed results of information technology (IT) investment made the investigation of user acceptance of IT increasingly challenging. A growing body of research in user acceptance of IT literature has limited focus on individual professionals as target users. It motivates researcher to use individual professionals as target users of IT acceptance, that are lecturers.